Cover Picture: Acid‐Responsive Absorption and Emission of 5‐N‐Arylaminothiazoles: Emission of White Light from a Single Fluorescent Dye and a Lewis Acid (ChemistryOpen 5/2016). Issue 5 (21st September 2016) - Yamaguchi, Kirara; Murai, Toshiaki; Guo, Jing‐Dong; Sasamori, Takahiro; Tokitoh, Norihiro
Abstract : The Front Cover picture shows structures of the key compounds and the change in the fluorescence. Although electron‐donating and ‐accepting groups of monocyclic 5‐ N, N ‐diarylaminothiazoles are not in the same plane but highly deviated, they show relatively strong fluorescence from blue to orange. In particular, the addition of Brønsted and Lewis acids to 5‐ N, N ‐diaryl‐2‐(4‐pyridyl)thiazoles shifts the absorption and emission to longer wavelengths. The thiazoles and acids form 1:1 complexes. Fine tuning of the amount of added B(C6 F5 )3 enables us to provide a white‐light emission with a single fluorescent molecule. More information can be found in the Communication by T. Murai and co‐workers onpage 434 in Issue 5, 2016 (DOI:10.1002/open.201600059 ).